(untitled) (مجلة دراسات إقلیمیة, 2026)
Iraq is a linguistically diverse country where languages from several language families are spoken. Prolonged political instability has led to internal displacement and migration, making it more difficult to understand the spatial distribution of these languages. In many parts of Iraq, linguistic documentation remains limited, whether in the form of language maps or other language-related studies. This study addresses this gap through the systematic documentation of the spatial distribution of linguistic communities in Al-Hamdaniyah District, Nineveh Province, northern Iraq. While earlier language maps relied largely on general knowledge and sources such as newspaper reports, this study combines specialized demographic and geographic records with firsthand fieldwork conducted across settlements in the district. For data visualization, the open-source GIS software QGIS was employed. The study produced a map showing the distribution of languages in Al-Hamdaniyah District. This map contributes to a better understanding of the region’s linguistic landscape, gives greater visibility to underrepresented linguistic communities, and assists in selecting representative locations for future comparative research on linguistic features using a language-data questionnaire.